(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2018)
The book of Enoch is one of the ancient compositions, which exists centuries before the birth of Christ and preserved only in the Gǝǝz language while it has been lost, for over 2,000 years in the world. Currently, Scholars of philology, ancient history, and Second Temple Judaism, and the Origins of Christianity are interested in studying the Ethiopic Book of Enoch. However, their primary objective is not to investigate the position of Enoch in Ethiopic literature rather enhance their knowledge of Jewish folklore and to seek information upon the religious ideas of Judaism, especially concerning the Messiah. Above all, the Enochic scholars in the west judged the Book of Enoch as a book of idolatry and magical practice‘. The general objective of this study, therefore, is focused on exploring the role of 1Enoch in the production of medieval Gǝǝz texts and investigating the themes of Enochic readings by analyzing words, lines, stanzas, and paragraphs of Enochic writings which might indicate the Ethiopian socio-religious context in which the book has been transmitted and used. Hence, both prose and poetic manuscripts are consulted. 1 ይህ ጽሑፍ ሇ3ኛ ዱግሪ ማሟያ ከቀረበ የምርምር ሥራ ተቀንጭቦ የተወሰዯ ነው፡፡ Haileyesus Alebachew Molaw (Ph.D.), Samara University, Addis Ababa, Ethiopia haileeoc@gmail.com ኤ.ቤ.ጥ.መ፣ቁ.፮(ነሏሴ፳፻፲) የኢትዮጵያ ቤተክርስቲያን ጥናት መጽሓት፣ ቁ.፮ (ነሏሴ ፳፻፲)፣Ó ጥናትና ምርምር ተ቉ም፣ማኅበረ ቅደሳን 2 Then, the quotations from Ethiopic Enoch explained in the light of the Book of Enoch accompanied by other liturgical and historical writings and annotated translations. The result showed that the Book of Enoch was frequently referred to and used as a source of Gǝǝz literature like in Mäṣәḥäfä Mәśțir, Mäṣḥäfä Bahәrәy, Mäṣḥäfä Bәrhan, Mäṣḥäfä ṩäḥäy, Mäṣḥäfä Sä‗atat, Dәrsanä ‘Ura ‘el, Mäṣḥäfä Sәnkәsar, ‘Ärke, Mälkkә‘ä Gubae, and Qǝne collections. The study, in general, showed that the fact that the presence of Ethiopic Book of Enoch in the Gǝ‗ǝz literature and the Book of Enoch itself doesn‘t have to do with idolatry and magical practice. Rather, in the post- Enochic literature we find the manifestation of refined theological points of view about Trinity, Christology, and Mariology.